Optimalisasi Hasil Belajar Pak dan Budi Pekerti Siswa Kelas VII Materi ‘Yesus Yang Berbelas Kasih’ dengan Metode Problem Based Learning SMP Budi Mulia Pematangsiantar - Herdin Lingga (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study is motivated by the low learning outcomes of students on the topic of "Jesus the Compassionate" in Grade VII at SMP Budi Mulia Pematangsiantar. To address this issue, the researcher applied the Problem-Based Learning (PBL) model with the aim of improving student learning outcomes. This research utilized a Classroom Action Research (CAR) methodology, conducted over two cycles. Each cycle consisted of two sessions and four stages: planning, implementation, observation, and reflection. The research subjects included 30 students from Grade VII. Data collection techniques involved documentation, observation, and tests. The results of this study indicate that the students' learning outcomes on the topic of "Jesus the Compassionate" showed significant improvement. In Cycle I, Session 1, 50% of students reached the "Developing" (BB) criterion. In Cycle I, Session 2, the students' performance increased to 74% under the "Adequate" criterion. In Cycle II, Session 1, 85% of students achieved the "Competent" criterion, and in Cycle II, Session 2, the students' performance further improved to 89% under the "Proficient" criterion. Therefore, it can be concluded that the use of the Problem-Based Learning (PBL) model effectively enhances the learning outcomes of students on the topic of "Jesus the Compassionate" in Grade VII at SMP Budi Mulia Pematangsiantar.